Ekstrak Daun Matoa (Pometia pinnata) sebagai Inhibitor Korosi Baja Karbon SS-304 - Fitria, Renny; Dahlan, Dahyunir; Syukri, Syukri (Jurnal Fisika Unand, 2024)
Research has been carried out on inhibitors from matoa leaf extract to inhibit the corrosion rate of SS-304 carbon steel. The Matao leaf extract used as an inhibitor was immersed in a 1 M H2SO4 corrosive medium. To determine the effect of inhibitor concentration and immersion temperature on steel corrosion, various inhibitor concentrations were varied, namely 0%, 1%, 2%, and 3% bt, and temperature variations, namely samples also in XRD and SEM characterization. 35°C and 40°C. The corrosion rate test was carried out using the weight loss method. The increase in the corrosion rate is in line with the increase in sample weight loss. The most efficient inhibitor of matoa leaf extract was obtained at a concentration of 3% with an immersion temperature of 35°C, namely 0.09 mmpy. The XRD results showed that the maximum peaks produced FeC and FeNi crystals, followed by FeO crystals. SEM characterization also showed that samples without inhibitors were more corroded, and samples using 3% inhibitor concentrations were slightly corroded.